BASKETBALL SCOUTING DURING AND AFTER GAMES (Fiep Bulletin - online, 2015)
The scouting technique-tactical is considered as a game statistics analysis, that allows measuring the athlete and teams ability. Garganta (2001) says that trainers and investigators have gotten excellent data concerning the factors related to a high level in the sport. Greco (1998) registers that scout technician-tacticians are very important for sport development in every aspect, in the beginning of the sport phase until high level. The technician with scouting can get to know potentialities and fragilities adversaries, by using this knowledge to reach the victory.  This study aims to evaluate technician importance attribution in basketball's scouting. For evaluation analysis, questions were elaborated and applied toward to technician, from feminine basketball team, which participated of 44º Jogos Abertos de Santa Catarina, in November of 2004.  During the games, it was elaborated teams scouts and delivered to technician, in the competition end, and between first and second period. We verified with questionnaire answers that 66.66% of the Technician had considered the use of scouting during the game as "very important", and 33.33% had considered "important".  Moreover, 83.33% of the technician says they use scouting for the development technique-tactical with their team aiming future competitions; and 16, 66 % confirm only to use it in some cases.  Rocha (1996) authenticates these data in his conclusions when he comments that scouting is a decisive operation for a competition to be able to work. We conclude that scouting can support the technician performance, aiming the players techniques movements and the tactical systems, showing up necessities and debilities that need to be developed in their team.
Keywords: BASKETBALL; SCOUTING; GAME ANALYSIS.